An Evaluation of the Impact of Monetary Easing Policies in Times of a Pandemic - Li, Ying; Sun, Yunpeng; Chen, Mengya (Frontiers in Public Health, 2021)
This article tests five major economies of the world, United Kingdom, Japan, Brazil, Chin and lastly, India, for the changes in the monetary policy decisions that have been implemented following the Covid-19 outbreak. The assessment was undertaken in the form of an event study analysis, further substantiated with a regression analysis conducted for exploring the significance of CPI and real GDP in predicting the policy interest rates in the economy. The results of the event study analysis presented that the abnormal changes in the interest rates were statistically significant in the case of the United Kingdom, Brazil and China, while the abnormal changes were found to be statistically insignificant in the case of India and Japan.